The Environmental Education Based on Atoni Pah Meto Culture - Saefatu, Meyrlin; Tanaem, Yusuf Elpontus; Pingak, Elizabeth Margareth (Sekolah Tinggi Teologi Sumatera Utara, 2023)
The issue of environmental damage has become a problem discussed by world leaders. The people of East Nusa Tenggara, especially Atoni Pah Meto really protect the environment. However, in recent years there has been manganese mining in their area which has caused damage to the environment where they live. Therefore, the aim of this study is to analyze environmental education based on local culture conducted by Atoni Pah Meto. This study uses a qualitative method with an ethnographic approach. The data collection technique used is the interview. Interviews were conducted with 15 people consisting of parents, children, Sunday school teachers, church administrators, and pastors. The results of the study show that Atoni Pah Meto embraces a local culture that states ‘land as mother’. When they intend to destroy nature, it means they are committing crimes with their own mothers. When they take anything from nature with the same greed they make their mothers cry. The life of Atoni Pah Meto appreciates nature more so that the relationship that is created between humans and nature is a relationship that is mutually beneficial and not detrimental to one party for the benefit of the other.